Identity and parentage of some South American grapevine cultivars present in Argentina. - Aliquó, Gustavo (2017)
Fil: Aliquó, Gustavo. Instituto Nacional de Tecnología Agropecuaria. Estación Experimental Agropecuaria Mendoza; Argentina.